2018
DOI: 10.1302/2046-3758.72.bjr-2017-0172.r1
|View full text |Cite
|
Sign up to set email alerts
|

The role of CKIP-1 in osteoporosis development and treatment

Abstract: Osteoporosis is a systemic skeletal disorder characterized by reduced bone mass and deterioration of bone microarchitecture, which results in increased bone fragility and fracture risk. Casein kinase 2-interacting protein-1 (CKIP-1) is a protein that plays an important role in regulation of bone formation. The effect of CKIP-1 on bone formation is mainly mediated through negative regulation of the bone morphogenetic protein pathway. In addition, CKIP-1 has an important role in the progression of osteoporosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…Recent studies demonstrate that CK2 interacting protein-1 (CKIP-1) plays an important role in the progression of osteoporosis [ 92 ]. Additionally, the CK2 inhibitor CX-4945 has been shown to promote osteoblastogenesis and inhibit osteoclastogenesis [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that CK2 interacting protein-1 (CKIP-1) plays an important role in the progression of osteoporosis [ 92 ]. Additionally, the CK2 inhibitor CX-4945 has been shown to promote osteoblastogenesis and inhibit osteoclastogenesis [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CKIP-1 inhibits both osteogenesis and adipogenesis via distinct mechanisms. [ 21 ] Previous studies have shown that CKIP-1 inhibits osteogenesis and osteoprecursor cells through Smurf1 ligase-mediated degradation of Smad1/5 and mitogen-activated protein kinase kinase 2. [ 8 , 22 ] In adipogenic differentiation, CKIP-1 interacts with the histone deacetylase 1 in the nucleus and inhibits the transcription of CCAAT/enhancer-binding protein α, which is a crucial adipogenic transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…At present, research on CKIP-1 mainly focuses on bone diseases. [14][15][16] Recently, the role of CKIP-1 in malignancies has attracted more attention. For example, studies have shown that CKIP-1 is a scaffold protein that may be involved in the tumorigenesis and progression of colorectal cancer, 5 non-Hodgkin's lymphoma 8 and glioma.…”
Section: Discussionmentioning
confidence: 99%